2022
DOI: 10.1021/acscatal.2c03858
|View full text |Cite
|
Sign up to set email alerts
|

Au(I) as a π-Lewis Base Catalyst: Controlled Synthesis of Sterically Congested Bis(triflyl)enals from α-Allenols

Abstract: A gold-catalyzed bis­[(trifluoromethyl)­sulfonyl]­ethylation of α-allenols, which allows the preparation of sterically congested bis­(triflyl)­enals bearing quaternary carbon centers, is presented. This sequence differs from the conventional reaction pathway of α-allenols under π-acid catalysis, because in our case Au­(I) functions as a π-Lewis base catalyst rather than a π-Lewis acid to activate the allene, facilitating the unusual addition of a carbon nucleophile of the gold complex belonging to the allenol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The rational assemblies of polyunsaturated systems, electrophiles, and nucleophiles, especially in a multicomponent manner, would significantly enrich the structural diversity and complexity of the products. Importantly, except for activating diverse polyconjugated systems in a vinylogous version, the potential expansion of π-Lewis base catalysis to more types of polyunsaturated substances, such as allenes , and alkynes, , still remains to be explored and mechanistically illuminated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rational assemblies of polyunsaturated systems, electrophiles, and nucleophiles, especially in a multicomponent manner, would significantly enrich the structural diversity and complexity of the products. Importantly, except for activating diverse polyconjugated systems in a vinylogous version, the potential expansion of π-Lewis base catalysis to more types of polyunsaturated substances, such as allenes , and alkynes, , still remains to be explored and mechanistically illuminated.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from Pd(0) catalysis, very few examples involving other metals as potential π-Lewis base catalysts have been reported. Recently, Almendros et al uncovered a gold-catalyzed bis­[(trifluoromethyl)­sulfonyl]-ethylation reaction between α-allenols 88 and 2-fluoropyridinium ethanide 89 , which represents a novel and efficient access to sterically congested bis­(triflyl)­enals 90 . Mechanism study indicated that the Au­(I) complex functioned as an uncommon π-Lewis base catalyst to increase the natural population analysis (NPA) charge of the central C3 atom of allenols 88 via regioselective η 2 -ligation, thus facilitating nucleophilic addition to Tf 2 CCH 2 generated in situ from Yanai’s betaine 89 .…”
Section: Other Metals As π-Lewis Base Catalystsmentioning
confidence: 99%